PENERBITAN KARTU NIKAH DI ERA DIGITAL PERSPEKTIF MASLAHAH - Zakiyatul Ulya (Indonesian Association of Islamic Family Law Lecturers, 2019)
Giving a marriage card together with marriage book for a married couple after the marriage contract is completed, as a consequence of the issuance of Peraturan Menteri Agama Nomor 19 Tahun 2018 tentang Pencatatan Perkawinan, has caused polemics among the public, especially regarding the urgency of issuing the card. In this case, some cicles consider that the issuance of marriage cards has a positive impact in facing demands in the digital era, especially in terms of efficiency, originality and data integration; on the contrary some other circles stated that the issuance of marriage card was not necessary given the existence of a marriage book so that it could potentially waste the budget, but this opinion was countered. If viewed from the aspect of its existence, the issuance of marriage cards includes maslahah mursalah because it is not all supported or rejected by the dalil syara’, but in line with syara law; in terms of the level of their needs, including maslahah hajiyah because it complements the existence of a marriage book so that it makes it easier to live life and eliminate the difficulties associated with hifdh al-nasl; in terms of its content, including maslahah ‘ammah because it relates to interests of the majority of Indonesian citezens; in terms of its content, including maslahah mah ammah because it relates to the interests of the majority of Indonesian citizens; and in terms of changes, including maslahah mutaghayirah because it allows for changes in human human needs related to proof of marital status in line with the changing era.